Switching costs impact on customer retention in telecommunication: An exploratory study in Lebanon. Issue 3 (September 2017) - Thoumy, Mira; Abdallah, Elie
Purpose: The purpose of this article is to assess the switching costs impact on the customer retention in the Lebanese telecommunication industry. Design/methodology/approach: Based on previous literature around customer retention and switching costs, a qualitative survey was conducted on one of the two operators managing the telecommunication market in Lebanon. Focus groups were organized to capture the point of view and perspective of top managers of the operator, results were then coded, and analyzed. Findings: Due to the current duopoly and status quo of the Lebanese telecommunication market, owned completely by the government and managed by two operators sharing the market equally and offering nearly the same portfolio, technologies and network coverage, the switching costs include only the time and effort needed to switch to the other operator, the financial fees to be paid upon buying a new subscription, the attachment to mobile number, and the relational loss from breaking bond with the current provider. Research limitations/implications: Focus group sessions were conducted with managers of one of the two telecom operators in Lebanon, and it might be relevant to interview the managers of the other operator as well. This topic was tackled from the provider's point of view; it would be interesting to check the customers' point of view. Practical implications: Managers in the Lebanese telecommunication industry can prepare marketing strategies including customer retention programs and well-designed switching costs to protect and increase their market share once this sector induces more competition either with the introduction of the number portability service or with the privatization of this sector in Lebanon. Originality/value: The customer retention and switching costs constructs are not yet studied in the Lebanese telecommunication market, and also due to the saturation in this industry, customer retention is becoming an imperative topic to all operators in this business.